2009
DOI: 10.1084/jem.20081633
|View full text |Cite
|
Sign up to set email alerts
|

Differential rates of replacement of human dermal dendritic cells and macrophages during hematopoietic stem cell transplantation

Abstract: Animal models of hematopoietic stem cell transplantation have been used to analyze the turnover of bone marrow–derived cells and to demonstrate the critical role of recipient antigen-presenting cells (APC) in graft versus host disease (GVHD). In humans, the phenotype and lineage relationships of myeloid-derived tissue APC remain incompletely understood. It has also been proposed that the risk of acute GVHD, which extends over many months, is related to the protracted survival of certain recipient APC. Human de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
216
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(236 citation statements)
references
References 75 publications
20
216
0
Order By: Relevance
“…Whereas human LCs seem to specialize in inducing cytotoxic CD8 + T cell responses, 37,38 human CD1a + DDCs, which constitute most of DDCs, mediate CD4 + T cell responses, 39 while CD14 + DDCs are proposed to promote antibody production by B cells through the induction of follicular helper T cells. 40 Compared with other crawl-out DC types, the CD14 + DDC subset expresses lower levels of the DC co-stimulatory molecules CD80 and CD86 and the DC maturation marker CD83, [41][42][43] which was also observed in this study. This maturation profile was accompanied by a lower T cell stimulatory capacity in comparison to other skin DC subsets, 40,41 which may be a reflection of the tolerogenic nature of this CD14 + DDC subset.…”
Section: Id-injected Vitd Selectively Induces the Migration Of Cd14supporting
confidence: 54%
“…Whereas human LCs seem to specialize in inducing cytotoxic CD8 + T cell responses, 37,38 human CD1a + DDCs, which constitute most of DDCs, mediate CD4 + T cell responses, 39 while CD14 + DDCs are proposed to promote antibody production by B cells through the induction of follicular helper T cells. 40 Compared with other crawl-out DC types, the CD14 + DDC subset expresses lower levels of the DC co-stimulatory molecules CD80 and CD86 and the DC maturation marker CD83, [41][42][43] which was also observed in this study. This maturation profile was accompanied by a lower T cell stimulatory capacity in comparison to other skin DC subsets, 40,41 which may be a reflection of the tolerogenic nature of this CD14 + DDC subset.…”
Section: Id-injected Vitd Selectively Induces the Migration Of Cd14supporting
confidence: 54%
“…Antibody AC-1A1 has been widely used to detect FXIII-A in cells and tissues by immunohistochemistry and immunofluorescence analysis [8,[17][18][19][20]. While we have confirmed that mAb AC-1A1 preferentially recognises FXIII-A positive cells in sections of embedded mouse heart, it strongly cross-reacts with off-target antigens in cultured cells, and so appears unsuitable for defining the subcellular trafficking of FXIII-A.…”
Section: Introductionmentioning
confidence: 41%
“…In human skin, three additional langerin-negative subsets of DCs have been identified, referred to as CD1a+, CD14+ and CD141 hi DCs [72][73][74]. Several studies have highlighted the potential of the different DCs subsets in influencing the direction of the immune response with the CD14+ DC subset being shown to preferentially induce a Th1-biased response [14,75] and to promote the secretion of large amounts of different immunoglobulins [14,76].…”
Section: Dendritic Cell Subsetsmentioning
confidence: 99%